Новые данные о желтой трясогузке (Motacilla flava L.) в Советских Карпатах - Черватюк, Т.В. (Вестник зоологии, 1969)
The data are presented on staying and nidification of Motacilla flava L. in the Rakhov massif of the Transcarpathian region. A female of this species was found on June, 11, 1962 near the upper-reaches of the Keveliv and the nest was detected for the first time on June 27, 1965 at the farm for cattle in the Menchul polonine. Growth and development of the nestlings were observed.